Состояние и тенденции развития технологий обеззараживания воды для питьевых целей - Рахманин, Ю.А.; Михайлова, Р.И. (Актуальні проблеми транспортної медицини, 2009)
В оглядовій статті надано аналіз досліджень щодо гігієнічного обгрунтування різноманітних технологій знезараження питної води, методології оцінки ризику, контролю якості води. The analysis of researches on a hygienic substantiation of various technologies of disinfection of drinking water, methodology of an estimation of risk, quality assurance of water is presented to in the review article.